Analisis Pengaruh Kualitas Pelayanan Jasa Terhadap Kepuasan Pelanggan: (Studi Pada Pelanggan Ojek Online) - Anindya Juraifa, Syalwa; Saniyya, Rona; Devintya Sari, Anggita; Noveto Pamella, Pancaly; Ricky, Martino (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to determine the level of service quality perceived by consumers on customer satisfaction provided by online motorcycle taxis through the dimensions of service quality which include physical evidence, reliability, responsiveness, assurance and empathy. The method used in this research is quantitative. While the data collection technique used in this quantitative research is to use a questionnaire, namely by distributing questionnaires or questionnaires to users of online motorcycle taxi services. Quisioners (questionnaires) are data collection techniques that are carried out by giving a set of questions or written statements to respondents to answer (Sugiyono, 2011: 142). In this case the author takes the object of research in 2022. Sampling uses the Random Sampling/Probability sampling method, where the number of samples taken is 38 respondents. The author distributes a questionnaire with 23 questions using the dimensions of physical evidence, reliability, responsiveness, assurance and concern. The types of tests used in this study are Instrument Tests, Classical Assumption Tests, Multiple Linear Regression Tests, Hypothesis Tests and Coefficient of Determination Tests. Based on the test results, the variables of physical evidence, reliability, responsiveness and assurance have no positive and significant effect on customer satisfaction, the empathy variable has a positive and significant effect on customer satisfaction.